Unreachable youth: physical education, national mobilization and intergenerational conflict in interwar Yugoslavia. The case of the Yugoslav Sokol - Papovic, Jovana (European review of history = Revue européene d'histoire, 2024)
For the Yugoslav Sokol, the leading organization dedicated to physical education in Interwar Yugoslavia, the youth was both an object and a tool of conquest. The education of younger generations was at the heart of its project of creating a new 'Yugoslav man' and a key asset in enforcing its legitimacy as an important agent in state-building. Yet, while the Sokol multiplied its initiatives to attract children and youth, these showed a contradictory interest in the organization. Moreover, besides the epic overtones of the official's narrative, intergenerational relations were often contentious: while the older representatives expected the younger ones to commit to the Yugoslav national project, the latter were frequently more interested in popular entertainment, and, even at times, in radical forms of political engagement. By critically analysing a diverse corpus of sources - publication and archives related to the Sokol's educational programmes together with different types of visual documents - as well as focusing on its local implementation in the Belgrade Sokol district, this article observes the discrepancies between the Sokol's ambitions and its reception on the ground, trying thus to shed light on the young people's experience and agency inside the organization.